Review on the production of effective plant biopolymers in reducing microbial infections - Jahantigh, Mojdeh; Larypoor, Mohaddeseh (Researcher Bulletin of Medical Sciences, 2023)
One of the most important problems from the past to the present is deadly opportunistic disease in developing countries, which leads to increase mortality in the world. Microbial pathogens such as fungi, bacteria, parasites, and viruses can cause these deadly opportunistic infections. Herbal medicines in the form of nanoparticles, nanocapsules, and biocompatible polymers, and liposomes can be effective in reducing mortality from these infections. Also due to the excessive use of antibiotics, microbial resistance is expanding day to day. On the other hand, indigenous, cheapness, availability, and rich source of effective herbal substances have made these compounds have many applications in biomedical fields. The aqueous extract, essential oil, and active ingredients of various parts of plants such as bark, stems, leaves, fruits, and seeds are used in the treatment of infectious diseases. This article provides information about medicinal plants that have antibacterial properties and are used to treat microbial infections. It is hoped that using this method can reduce and treat microbial infections to some extent.